Peluang dan Tantangan Pemanfaatan Frekuensi Ka-Band untuk Sistem Komunikasi Satelit [Opportunities and Challenges upon Usage of Ka-band Frequency for Satellite Communication System] - Wirianto Pradono (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2017)
Data traffic growth is much higher than that of voice traffic. Cisco predicts that mobile data traffic in Indonesia will grow 8- fold from 2016 to 2021. Broadband technology becomes appropriate solution to cope with data traffic growth and to keep quality of service optimal. Considering that terrain profile of rural areas in Indonesia is hard for terrestrial system to be deployed, satellite technology is urgently required to deploy broadband services in rural areas. Considering its superiorities over existing satellite systems, Ka-band satellite is one of key technologies to enable broadband service penetration in rural area. Literature studies and qualitative approach are used in this study to identify opportunities and challenges Indonesia will encounter when deploying Ka-band satellite system. Research results show that Ka-band satellite is capable of facilitating telecommunication services requiring high bandwidth. Satellite service users also vary, spanning from industries, government agencies, and consumers. Regardless superiorities Ka-band satellite offers, there are still some challenges to address. Those challenges are vulnerability of Ka-band frequency due to rain attenuation and lack of Ka-band filing owned by Indonesia with status approved by International Telecommunication Union (ITU). *****Pertumbuhan trafik data jauh melampaui pertumbuhan trafik suara. Cisco memprediksi trafik data bergerak di Indonesia akan meningkat sebesar 8 kali lipat dalam periode 2016-2021. Teknologi pitalebar merupakan solusi tepat untuk memfasilitasi peningkatan trafik data sekaligus menjaga kualitas layanan tetap optimal. Kondisi medan wilayah rural Indonesia sulit dijangkau oleh sistem terestrial sehingga teknologi satelit sangat dibutuhkan agar penetrasi layanan pitalebar dapat menjangkau wilayah tersebut. Menimbang sejumlah keunggulan dari satelit Ka-band dibandingkan sistem satelit yang ada saat ini membuat satelit Ka-band menjadi salah satu teknologi kunci yang memungkinkan penetrasi layanan pitalebar hingga wilayah rural. Studi literatur dan pendekatan kualitatif digunakan dalam studi ini untuk mengidentifikasi potensi dan tantangan yang dihadapi Indonesia dalam pengembangan sistem satelit Ka-band. Hasil studi menunjukkan satelit Ka-band mampu memfasilitasi layanan telekomunikasi yang membutuhkan bandwidth besar. Pengguna layanan satelit juga bervariasi meliputi industri, institusi pemerintah, hingga konsumen individu dan rumah tangga. Meskipun satelit Ka-band menawarkan sejumlah keunggulan, ada beberapa tantangan yang harus diantisipasi yakni kerentanan frekuensi Ka-band terhadap redaman hujan dan ketiadaan filing Ka-band milik Indonesia dengan status disetujui oleh International Telecommunication Union (ITU).